KEPUASAN PELANGGAN TOKO ONLINE YANG DIPENGARUHI KUALITAS PRODUK DAN LAYANAN - T. Husain; Asrul Sani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
Online shopping is a new form of communication that does not require a face-to-face meetings. If consumers get good service rights, then the added value for a company that will make consumers will continue to make transactions at that place. The trust of a customer is very important for an online company. A customer must have a positive attitude towards the online store. The method used in this research is the positivistic method based on the philosophy of positivism. The data will be used in the form of numbers and analysis using statistics in order to explain the causal relationship to be examined. This research can be used as input and performance evaluation related to service quality and product quality on trust to achieve customer satisfaction in an online store.